Caracterização da estrutura vertical e do dossel de um fragmento de Floresta Ombrófila MistaVertical structure and canopy characterization of a mixed Ombrophyla Forest fragment - Côrte, Ana Paula Dalla (2009)
A Floresta Ombrofila Mista, também conhecida como Floresta de Araucária é caracterizada pela presença da Araucaria angustifolia no dossel superior da floresta, acompanhado pela imbuia e demais espécies da família das lauráceas no estrato intermediário e outras espécies de folhosas como a Ilex paraguariensis no estrato inferior. Neste trabalho, realizou-se uma avaliação da estrutura do dossel através da plotagem da projeção das copas de todos os indivíduos presentes em uma parcela de 1 hectare localizada no município de São João do Triunfo, estado do Paraná, Brasil. Foram medidos 644 indivíduos, sendo 226 de araucária, 99 de canelas, 10 de Imbuia e 309 de outras espécies de folhosas, sendo que o somatório das projeções das copas representou 166,5% de cobertura do terreno. Do somatório da cobertura total, observou-se que 65% dizem respeito as copas de Araucaria angustifolia, 22,7% das Canelas, 2,8% das imbuia e 76% das outras espécies. Ainda, a araucária ocupou, principalmente, o estrato superior, a imbuia e canelas dividem o estrato intermediário e outras espécies folhosas compõem o estrato inferior. Concluiu-se que é necessário avaliar outros fatores que condicionam o desenvolvimento da floresta e são afetados pelo dossel, como a luminosidade no interior do sub-bosque as áreas de clareiras, a fim de se obter subsídios para uma melhor compreensão da estrutura da floresta.Abstract The Mixed Araucaria Forest, also known as Araucarian Forest, distinguish itself by the presence of the Araucaria angustifolia in the primary stratum of the forest, followed close, in the intermediate stratum, by the specie commonly known as Imbuia and further other species from the Lauraceae family, and many other deciduous tree species as the Ilex paraguariensis in the lower stratum of the forest. This paperwork presents an evaluation that studied the canopy structure of an Araucarian forest, by representing the crown projection of all the trees encounter in a total area of 1 hectare (2,47 acres), in a drawing plot, carried out in the county of São João do Triunfo, State of Paraná, Brazil. Out of a total of 644 numbered trees, 226 belonged to Araucaria, 99 trees were classifi ed as belonging to the Lauraceae family, 10 trees were classifi ed as being Imbuia and the remaining 309 individuals, were found to be from different deciduous tree species. From the calculation of the total area covered by the crown projections of trees, that reached 166,5%, Araucaria showed to occupied 65% of the area of all the crown projections, species from the Lauraceae family, Imbuia and the deciduous trees respectively reached, 22,7%, 2,8% and 76%. Even more, the Araucaria had mainly been identified in the primary stratum of the forest, the Imbuia and the species from the Lauraceae family were found to be sharing the intermediate stratum, and finally the deciduous trees presented a majority of trees in the lower stratum. It is concluded that it is a necessity, for a further understanding of the canopy structure of the forest, that scientific investigations should continue to analyze factors that both infl uence the forest evolution and, which have direct relationship with the canopy, as for example the brightness inside forests and gaps.